EXPLICITATION STRATEGY IN TRANSLATING AN INDONESIAN NOVEL INTO ENGLISH - Mahmud, Erlina Zulkifli; Sobarna, Cece (Lire Journal (Journal of Linguistics and Literature), 2023)
TThis research article is about the use of translation strategy namely explicitation in the translation of a novel from Indonesian into English. The data source is an Indonesian novel entitled Lelaki Harimau written by Eka Kurniawan and its English translation, Man Tiger. The novel creates commands and critics regarding its content as well as its language use. This makes the novel unique. The uniqueness in the source language text needs extra works to do in delivering the closest natural equivalent in the target language text. Untranslatability is no longer issue as there are strategies of translation that can be applied, one of them is explicitation. The explicitation strategy used is the one proposed by Klaudy. Using descriptive qualitative method, this research is aimed at revealing the kind of information being explicitated, the forms of explicitation used, and the semantic information of the words explicitated. The results show that the kind of information is both cultural and non-cultural, and the forms of explicitation identified are all five of them and semantically all the words being explicitated become clearer, specific, and more informative.